تقويم المهارات اللغوية - A. Rani, Samsuar (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
To know how far lesson objectives are met, a teacher or an institution need to gather accurate information relating to the result of the learning process. Thesedata are normally obtained by using instruments such as tests, questionnaires, interviews, and observations. Assessment is all the methods used to collectinformation about the knowledge, ability, understanding, attitude, and motivation of the students that can be performed through tests or selfassessmentseither formally or informally. Test is a procedure that can be used to assess student’s performance. Test can be objective or subjective. To know students’ language ability, it should be obtained from an evaluation or a test using a proper instrument. This paper shall discuss how it should be conducted in evaluating Arabic skills covering listening, speaking, reading, and writing.